Growth and Anchorage of Myriophyllum spicatum L. in Relation to Water Depth and the Content of Organic Matter in Sediment - He, Liang; Wang, Rui; Zhang, Huan; Zhang, Meng; Liu, Ying; Zhu, Guorong; Cao, Te; Ni, Leyi; Ge, Gang (Frontiers in Environmental Science, 2021)
A large body of evidence suggests that the physical and chemical characteristics of the sediment in lakes that have undergone eutrophication have been significantly altered. However, the effects of alterations in sediments on submersed macrophytes remain unknown. In this study, we present the results of an outdoor experiment that examined how the growth and anchorage of the widespread submersed macrophyte Myriophyllum spicatum L. responded to the enrichment of organic matter in the sediments and whether the water depth affects these responses. We found that low levels of enrichment with organic matter (≤ 7%) enhanced the growth of M. spicatum. In contrast, high levels of enrichment with organic matter (from 12% to 18%) slightly inhibited its growth. Although the anchorage force of M. spicatum slightly decreased with an increase in the content of organic matter in the sediment, it was much higher than the hydraulic drag force on plants at a relatively high current velocity, indicating that the plants were unlikely to be uprooted in these sediments. The water depth did not alter the responses of growth and anchorage of M. spicatum to enrichment with organic matter. Our results suggest that M. spicatum could be a potential species to restore eutrophic lakes, since it can grow well and anchor stably in sediments with relatively high organic matter and manage low light stress.